1973
DOI: 10.1139/m73-225
|View full text |Cite
|
Sign up to set email alerts
|

The physiology of teichoic acid deficient staphylococci

Abstract: Cell walls isolated from a teichoic acid deficient mutant (52A5) of Staphylococcus aureus strain H were found to have lower capacities to bind cations than did walls of the parent strain. Both types of walls had higher binding affinities for Mg2+ and Ca2+ than for K+ and Na+. The reduced number of phosphate groups in 52A5 walls was reflected in a higher apparent pKa of 4.3 for displacement of Mg2+ (or Ca2+) during acid titration with HCl. The comparable pKa value for displacement of bound Mg2+ from parent-stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1974
1974
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…It was therefore argued that the teichoic acid in the parent strain did not play a vital role in sequestering Mg2+ from the environment. In our view such a conclusion is unjustified since it is clear from the results of Ou et al (1973) that the teichoic acid-deficient mutant bound a measurable amount of Mg2+ which could well have been sufficient to meet the requirements of the cells under the conditions studied. Similar studies on a teichoic acid-deficient mutant of S. aureus isolated in this laboratory have shown that Mg2+ ions are significantly bound to carboxyl groups of an anionic polymer in the cell wall (A. R. Archibald, personal communication).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…It was therefore argued that the teichoic acid in the parent strain did not play a vital role in sequestering Mg2+ from the environment. In our view such a conclusion is unjustified since it is clear from the results of Ou et al (1973) that the teichoic acid-deficient mutant bound a measurable amount of Mg2+ which could well have been sufficient to meet the requirements of the cells under the conditions studied. Similar studies on a teichoic acid-deficient mutant of S. aureus isolated in this laboratory have shown that Mg2+ ions are significantly bound to carboxyl groups of an anionic polymer in the cell wall (A. R. Archibald, personal communication).…”
mentioning
confidence: 84%
“…questioned by some authors (Ou et al, 1973;Doyle et al, 1974). Studies on the physiology of a teichoic acid-deficient mutant of Staphylococcus aureus showed that although the cells had a decreased capacity for binding Mg2+ compared with the parent strain they did not display increased sensitivity to Mg2+ depletion (Ou et al, 1973). It was therefore argued that the teichoic acid in the parent strain did not play a vital role in sequestering Mg2+ from the environment.…”
mentioning
confidence: 99%
“…One of these, strain 52A5, has both a reduced capacity and a lower affinity for cations (320,377). It grows 30% slower than the wild type, and cell separation is defective.…”
Section: Mutants Defective In Lta and Wta Assemblymentioning
confidence: 99%
“…The interpretation of these results in cation assimilation and binding has been the focus of some discussion (133,134,289,377). However, high affinity for divalent cations in the wall matrix would be counterproductive and thus would work against the corresponding cation transport system of the cell (e.g., the Mg 2ϩ transporter [348]).…”
Section: D-alanyl Esters In the Binding Of Ligandsmentioning
confidence: 99%
“…Hughes et al (18) proposed that teichoic acids, by virtue of their divalent cation binding ability, function to sequester necessary ions for cation-dependent membrane enzymes. However, more recent evidence from experiments with teichoic acid-deficient staphylococci demonstrates that teichoic acid does not significantly bind divalent cations (27). Teichoic acid-free mutants of bacilli frequently possess bizarre morphologies (40).…”
mentioning
confidence: 99%